Kinetics and dynamics of development of children and adolescents in Poznań - Kaliszewska-Drozdowska, Maria Danuta; Malinowski, Andrzej (Anthropological Review, 1975)
On ground of anthropometric measurements of 3,152 individuals in age from 3 to 18 years taken in randomly chosen kindergartens, primary and high schools from Poznań city in the years 1971/72 present day state of physical development of subadults is presented.Analysing dynamics of physical development of examined individuals and age changes in sexual dimorphism authors have found adolescent growth spurt to be at 15 - 16 years in boys and 10 - 12 in girls.